Cell Phone Policy in a Public High School - Holley, Dorothy; Park, Soonhye (Journal of Management Policy and Practice, 2020)
The purpose of this study is to examine teachers’ experiences and perceptions of their cell phone policies created and implemented in their own high school classrooms. This study represents one high school in a southeast state of the U.S. after two years of teacher autonomy in creating and enforcing his/her own cell phone policy. Four themes emerged from teacher surveys (N=71) and teacher interviews including student challenges and learning, instructional workload, institutional culture and support, and alignment of technology with policy. Strategies and recommendations highlight the need for teachers’ voices in policy decisions impacting teachers and students.